(untitled) (Internet of Things and Edge Computing Journal, 2022)
The rapid development of Internet of Things (IoT) technology has opened up new possibilities in healthcare, particularly in remote areas where access to traditional healthcare services is limited. This paper explores the emerging trends in leveraging IoT devices to improve healthcare accessibility in remote areas. We discuss the challenges faced in providing healthcare services in such areas and how IoT devices can address these challenges. We also examine the various applications of IoT in healthcare, including remote patient monitoring, telemedicine, and health data analytics. Additionally, we discuss the potential impact of IoT on healthcare accessibility and the challenges that need to be addressed to fully realize this potential.